Mendalami Sistematis Ayat dan Surat Untuk Memantapkan Karakter Islami - Rahim, Raficha; Putri, Rahmadila; Arika, Syahfitri (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research examines the systematic arrangement of verses and chapters in the Quran and its impact on shaping Islamic character, especially among Muslim children in Indonesia. The study focuses on whether this arrangement is tauqify, ijtihady, or both of them, aiming to understand its role and influence in forming a strong Islamic character.Knowledge of this systematic arrangement positively influences the formation of Islamic character in Muslim children. Amid technological advancements and easy access to information, a proper understanding of the structure of verses and chapters in the Quran can counter Orientalist views that doubt the Quran's arrangement. The research employs literature or library research, drawing from existing works and selecting relevant data.The method used in writing is qualitative. Findings indicate that the systematic arrangement of verses and chapters in the Quran is tauqify, and a good understanding significantly contributes to building a strong Islamic character among Muslim children in Indonesia. Consequently, this research makes a positive contribution to preserving the authenticity of Islamic teachings and strengthening the foundation of Islamic character in the younger generation.